Investigation of bending properties of E-Glass fiber reinforced polymer matrix composites for applications in micro wind turbine blades. (February 2020) - Singh, Sachidanand; Hanumantharaju, H.G.; Teja Yadla, Sai Ravi; Hemanth Rao Yadav, S; Srivatsa, Shreyas
Abstract: Polymer matrix composites are divided into thermoplastic or thermosetting polymers reinforced with organic or inorganic fiber. Use of composites is increasing in the field of engineering applications due the fact that they are satisfying the required mechanical properties. The present study is made on Sandwich composite with E-Glass fiber reinforced Epoxy composite skin and Balsa wood core. E-Glass fiber reinforced composite is an immensely versatile material due to its light weight, inherent strength, weather resistance, finish and also due to variety of surface textures. Though carbon fibers are more rigid then eglass fiber, we choose e-glass for its lower cost and are better suited to extreme flex patterns. The composite consist of E-Glass fiber, epoxy resin namely Ly556 and Hardener 951. E-glass is a low alkali glass with a typical nominal composition of SiO2 54wt%, Al2O3 14wt%, CaO+MgO 22wt%, B2O3 10wt% and Na2OK2O less then 2wt%. Some other materials may also be present at impurity levels. Tensile test, compression test and three point bending test etc. has to be carried out to better understand the mechanical properties of composite material. In this study three point bending test is discussed. This study is done keeping in mind the use of E-Glass fiber and epoxy resin composite in micro wind turbine blade.